The Scientist's World - Davis, Bernard D. (American Society for Microbiology, 2000)
This paper describes the features of the world of science, and it compares that world briefly with that of politics and the law. It also discusses some “postmodern” trends in philosophy and sociology that have been undermining confidence in the objectivity of science and thus have contributed indirectly to public mistrust. The paper includes broader implications of interactions of government and science.